Analysis of trigeminal nerve disorders after oral and maxillofacial intervention - Ghassemi Alireza; Stein Jamal M; Esteves-Oliveira Marcella; Grosjean Maurice B; Koch Felix; Said Yekta Sareh; Riediger Dieter; Lampert Friedrich; Smeets Ralf (Head & Face Medicine, 2010)
Abstract Background Quantitative sensory testing (QST) is applied to evaluate somatosensory nerve fiber function in the spinal system. This study uses QST in patients with sensory dysfunctions after oral and maxillofacial surgery. Methods Orofacial sensory functions were investigated by psychophysical means in 60 volunteers (30 patients with sensory disturbances and 30 control subjects) in innervation areas of the infraorbital, mental and lingual nerves. The patients were tested 1 week, 4 weeks, 7 weeks and 10 weeks following oral and maxillofacial surgery. Results QST monitored somatosensory deficits and recovery of trigeminal nerve functions in all patients. Significant differences (p < 0.05) between control group and patients were shown for cold, warm and mechanical detection thresholds and for cold, heat and mechanical pain thresholds. Additionally, QST monitored recovery of nerve functions in all patients. Conclusion QST can be applied for non-invasive assessment of sensory nerve function (Aβ-, Aδ- and C-fiber) in the orofacial region and is useful in the diagnosis of trigeminal nerve disorders in patients.